Synthesis of (−)‐Hebelophyllene E: An Entry to Geminal Dimethyl‐Cyclobutanes by [2+2] Cycloaddition of Alkenes and Allenoates. (24th March 2018) - Wahl, Johannes M.; Conner, Michael L.; Brown, M. Kevin
Abstract: The first synthesis of hebelophyllene E is presented, along with assignment of its previously unknown relative configuration through synthesis of epi‐ent ‐hebelophyllene E. Development of a catalytic enantioselective [2+2] cycloaddition of alkenes and allenoates provides access to the required chiral geminal dimethylcyclobutanes. Key to its success is the identification of a novel oxazaborolidine catalyst which promotes the cycloaddition in high enantioselectivities with good functional‐group tolerance (9 examples, up to 97:3 e.r.). Thus, a late‐stage cycloaddition using a fully functionalized alkene, followed by a diastereoselective reduction allows a concise entry to this class of natural products. Abstract : Aufklärungsarbeit : Die erste Synthese von Hebelophyllen E wird vorgestellt, ebenso wie die Zuweisung dessen zuvor unbekannter relativer Konfiguration über die Synthese von epi‐ent ‐Hebelophyllen E. Eine katalytische enantioselektive [2+2]‐Cycloaddition von Alkenen und Allenoaten, gefolgt von einer diastereoselektiven konjugierten Reduktion, bot Zugang zu dem benötigten chiralen geminalen Dimethylcyclobutan‐Kern.